Political institutions and finance-growth nexus in emerging markets and developing countries: a tale of one threshold - Slesman, Ly; Baharumshah, Ahmad Zubaidi; Wan Ngah, Wan Azman Saini (Elsevier, 2019)
The empirical evidence predicts that political institutions are the core component of institutional matrix. They set stages for other institutions to be devised and influence the economic growth. Applying Kremer et al.’s (2013) dynamic panel threshold regression to a selected panel of 77 emerging market and developing countries over the period 1976–2010, we provide compelling evidence in favor of a split base on political institutions in the finance-growth nexus. The asymmetric impact of institutions on growth sets in around the optimum threshold level. Minimizing political risks through improvement in the quality of political institutions can improve the growth dividend due to financial development. Our empirical results appear to be robust across a wide range of alternative empirical strategies, several new disaggregate measures of political institutions, and also when addressing the endogeneity issues of the regressors.